IDEOLOGI PERLAWANAN DALAM ANTOLOGI PUISI FĪ ṬARĪQI AL-FAJRI KARYA ABDULLAH AL-BARADDUNI - Zulfa Purnamawati; Sangidu Sangidu; Fadlil Munawwar; Taufiq Dardiri (POETIKA, 2019)
Artikel ini bertujuan untuk mengungkap ideologi perlawanan dalam antologi Puisi Ilā Ṭarīqi al-Fajri (Menyongsong Fajar) yang diciptakan pada tahun 1960-1979 oleh Abdullah al-Baraddūnī seorang penyair buta asal Yaman Utara. Untuk mengungkapkan Ideologi perlawanan dalam antologi tersebut digunakan kritik sastra materialistik yang disampaikan oleh Terry Eagleton. Adapun meteode yang digunakan adalah metode dialektik, yaitu pembacaan timbal balik antara elemen internal puisi tersebut dengan elemen-elemen eksternal. Puisi-puisi dalam antologi ini diciptakan saat Yaman Utara berada di bawah kekuasaan dengan ideologi Imamah Zaidiyyah yang bertindak sewenang-wenang dalam menjalankan kekuasaannya. Puisi dipilih sebagai genre untuk mengungkapkan ideologi perlawanan karena kondisi pengarang yang buta, produksi sastra di Yaman Utara yang menjadikan puisi sebagai sastra rakyat, dan kondisi sosial Yaman yang sebagian besar penduduknya masih buta huruf. Perlawanan dalam puisi-puisi tersebut adalah perlawanan rakyat terhadap pemerintahan imamah yang telah berlaku sewenang-wenang terhadap rakyat sehingga hak kebebasan, hak politik, dan hak ekonomi rakyat tidak terpenuhi. Sebagai puncaknya adalah revolusi yang menuntut digantinya ideologi imamah dengan ideologi republik yang memberikan ruang kepada rakyat untuk terlibat dalam persoalan negara dan kehidupan yang lebih baik.Kata kunci: ideologi perlawanan; kritik sastra materialistik; Imamah Zaidiyyah; Yaman Utara This article attempts to explore the ideology of resistance in the poetry anthology Ilā Ṭarīqi al-Fajri (On the Path of Dawn) was created in 1960-1979 by Abdullah al-Baraddūnī, a blind poet from North Yemen. The ideology of resistance in this anthology was analyzed by using materialist literary criticism, which was used by Terry Eagleton. The method used in this study is the dialectical method, namely reciprocal reading between the internal elements of the poem with external elements. The poems were created  when Yemen was under control the Zaydi Imamate, who arbitrarily exercised his power. The poetry was chosen as a genre to express the ideology of resistance because of the conditions of blind poet, literary production in North Yemen which made poetry as a folk literature, and the social conditions of Yemen, where the majority of the population was illiterate. The ideology of resistance in this anthology is resistance to the arbitrariness of the ruling government, which did not recognize freedom rights, political rights and economic rights of the people of North Yemen. In addition, there was a resistance to the ideology of Imamate.The ideology of Imamate was replaced by an ideology of the republic which provided space for the people of North Yemen to participate in the management of the country and to pursue a more prosperous life.Keywords: ideology resistance; materialist literary criticism; Zaydi Imamate; North Yemen